Race determination based on nonmetric teeth morphological traits - Siritta Kalistu; Nagabhushana Doggalli; Karthikeya Patil; Sushma Rudraswamy (Wolters Kluwer Medknow Publications, 2019)
The relationship between dental morphological traits and ancestry has received the utmost amount of attention from dental anthropologists and forensic odontologists. Caucasoid, Mongoloids, and Negroid are the chief racial groups of the world. The dentition of each race has been reported to be unique to its race and has been employed to determine ancestry. Unfortunately, over the years, the concept of race has been fading away due to hybridization between races worldwide. Hence, one cannot solely rely on dental morphological traits to assign a race to an unknown. Nevertheless, even though dental morphological traits have been blended among the three races, there are still those traits that are dominant in one or the other ethnic group.